Differentiating children through education: school choices and educational practices of middle-class families in neoliberal times - Çimen, Canan Aratemur. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
This research examines school choices and educational practices of middle-class families within the context of neoliberalization. The aim is to understand the ways in which their dispositions in education contribute to the creation of class advantage, class distinctions and increasing inequalities in a society. The data was collected mainly through in-depth interviews with parents, administrators and teachers in two selective high schools –one public and one private high school–in Istanbul. The findings indicate that reproduction of the middle class on the basis of education is highly dependent on the mobilization of economic, cultural and social capital of the families with extensive efforts of mothers. Since families have a high sense of responsibility for directing children’s education in the right way and making up differentiated children, they become more responsive to market signals in trying to find the best schools and the best ways to support the academic and individual development of their children. In this process, parents’ desires, dispositions and choices are shaped by the rationality of neoliberalism and those who continuously invest in children for enhancing their economic and social well-being turn into “active, responsible, competitive and entrepreneurial” subjects. After all, since their educational strategies and practices contribute to a social boundary-making process, middle-class families continue to retain their key roles in the creation and reproduction of class-based distinctions within the context of neoliberalization.
Keywords: Middle class families -- Turkey.; Education -- Turkey.; Neoliberalism.